Evaluation of an intercultural exchange program: an example of the experience of elementary school students and their parents - Drljaca, Isidora; Perić Prkosovački, Bojana (Norma, 2025)
This paper presents an analysis of the influence of an intercultural student exchange program on the participants and their families, regardless of whether they come from small or large communities. The aim of this paper is to highlight the importance of student intercultural exchanges for identifying individual needs and fostering identity disclosure, developing intercultural empathy, overcoming stereotypes and prejudice, and training students for teamwork with people from diverse cultural backgrounds. Enabling youth to share their positive experiences with their surroundings, thereby creating a broader social impact, fostering inclusivity, and contributing to the development of a more diverse and open world, are of particular importance. For the purpose of this research, a sample of 42 project participants (seventh-grade students) and 36 parents was used. The results show that participants and their families understand the importance of intercultural exchanges and that they continue to advocate for their further implementation in formal education, regardless of the participants’ background. However, some common opinions about particular aspects of intercultural exchanges can be observed among groups from similar backgrounds.